Cryoprotection of Modified Erythrocytes with Polyethylene Glycol and Dextran - Ramazanov, V. V.; Olejnik, O. A.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2005)
There was investigated the effect of preliminary cytoskeletal modification on the integrity of erythrocytes, frozen with polyethylene glycol (PEG) and dextran, as well as on dynamics of their lysis after resuspending in isotonic media with different anions (chloride, sulfate, citrate). Integrity of modified erythrocytes after freezing with PEG was shown to be higher if comparing with dextran. At the same time resuspension of frozen-thawed erythrocytes in the media with different anions testifies to the fact, that cells, frozen with PEG are less osmotically resistant and lysis curves in the media with various anions are less different than with dextran. The results obtained confirm, that dextran, in comparison with PEG in a greater extent retains the development of damages in membranes during freezing, which are initiated by erythrocyte treatment with cytoskeletal modifiers.